Towards a New Solution of the Butt of Malmsey Problem - Dalby, Andrew (Petits Propos Culinaires, 2015)
The articles looks at the evidence that Edward IV eliminated his brother, Clarence, by causing him to drown in a butt of Malmsey and offers an explanation of why that particular wine.